1978
DOI: 10.1097/00000658-197809000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Vascular Surgery

Abstract: Preoperative and intraoperative antibiotic prophylaxis of infection in peripheral vascular surgery has been widely used although controlled studies have been lacking. A randomized, a prospective, double-blind study of cefazolin versus placebo during 565 arterial reconstructive operations was performed at this hospital from February 1976 through August 1977. Among the 462 patients undergoing surgery of the abdominal aorta and lower extremity vasculature, there was a highly significant difference in the infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(68 citation statements)
references
References 13 publications
0
68
0
Order By: Relevance
“…Since existing vascular access infection rates occur in the setting of topical antibiotic use, any further decrease in infection rates will most likely result from some additional route of antibiotic delivery. While systemic prophylactic antibiotics have been shown to work with vascular graft infections, no one has investigated the use of systemic antibiotics to prevent vascular catheter infection (11,16). However, there are data suggesting that the use of regionally delivered antibiotics (i.e., catheter-bound antibiotic) is effective at decreasing vascular infection (6,19).…”
Section: Methodsmentioning
confidence: 99%
“…Since existing vascular access infection rates occur in the setting of topical antibiotic use, any further decrease in infection rates will most likely result from some additional route of antibiotic delivery. While systemic prophylactic antibiotics have been shown to work with vascular graft infections, no one has investigated the use of systemic antibiotics to prevent vascular catheter infection (11,16). However, there are data suggesting that the use of regionally delivered antibiotics (i.e., catheter-bound antibiotic) is effective at decreasing vascular infection (6,19).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, because primary prophylaxis is such a long established standard of care and infections are associated with a high morbidity and mortality, patients and healthcare providers might understandably be reluctant to participate in placebocontrolled studies. Kaiser et al 296 reported a controlled, randomized, prospective, double-blinded study in patients undergoing clean vascular graft surgery that compared placebo (237 patients) with perioperative cefazolin (225 patients). There was a significantly (P<0.001) higher rate of wound infections among the placebo group (6.8%) than among the cefazolin recipients (0.9%).…”
Section: Primary Prophylaxismentioning
confidence: 99%
“…[296][297][298] There are insufficient published data to recommend vancomycin for perioperative prophylaxis. It is unlikely that placebo-controlled, blinded studies will be published for primary prophylaxis in patients who undergo endovascular device placement; however, the administration of a perioperative β-lactam antibiotic may be considered.…”
Section: Primary Prophylaxismentioning
confidence: 99%
“…Cefazolin has been considered ideal for this purpose because of its pharmacokinetic properties and broad-spectrum antimicrobial activity. Well-designed, placebo-controlled trials have demonstrated that cefazolin reduces the incidence of postoperative wound infections in comparison with placebos in patients undergoing vascular surgery (13) and total hip replacement (11 (14,19,28). The smaller study by Meszaros and colleagues (19) can be criticized because significant differences between treatment groups were apparent only when all infections were included.…”
Section: Introductionmentioning
confidence: 99%